An examination of the chlorophyll-phosphorus relationships of lakes, rivers and estuaries. - Champion, Michelle (University of Ottawa (Canada), 1999)
The residual variability surrounding chlorophyll a---total phosphorus (Chl-TP) relationships decreases the predictive ability of phosphorus loading models to forecast algal biomass production in lakes. In the first section of this thesis I attempt to account for the residual variation in chlorophyll a concentration by examining how the sequestration of phosphorus into non-algal compartments of the water column varies among aquatic biomes. This is achieved by examining the relationships between chlorophyll a and various chemical forms (particulate, soluble, organic and inorganic) and size classes (total, >64mum, 30--64mum, 3--30mum, 0.2--3mum) of phosphorus. In the second section, I examine if the much lower than expected chlorophyll yield of Prince Edward Island (PEI) estuaries is the result of mussel grazing and/or increased turbidity or if it is the result of a general regional effect caused by the Island's geological characteristics. This latter hypothesis implies that PEI lakes and rivers would also possess lower chlorophyll yields. This question is examined by comparing the data from each of the PEI biomes (lakes, rivers, estuaries) with that of reference set possessing the expected chlorophyll a to total phosphorus ratio. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.